Rheumatoid factor and anti-citrullinated peptide antibodies in the general population: hepatitis B and C virus association and 15-year-risk of rheumatoid arthritis - Generali, Elena; De Santis, Maria; Isailovic, Natasa; Palermo, Bianca; Guidelli, Giacomo Maria; Ceribelli, Angela; Alborghetti, Fausto; Colloredo, Guido; Porrati, Luisa; Matthias, Torsten; Zucchi, Alberto; Selmi, Carlo (Clinical and experimental rheumatology, 2021)
The study aimed to determine the prevalence of rheumatoid factor (RF) and anti-citrullinated peptides (ACPA), to estimate the association with hepatitis B (HBV) or C (HCV) virus infections and the 15-year risk of developing RA in a large cohort from a Northern Italian region. In 1998, 15,907 subjects between the ages of 18 and 75 were randomly selected 1:4 for HBV and HCV testing; more recently, we tested a subgroup of sera for RF (n=2196) and ACPA (n=2525). Administrative databases were searched after 15 years for incident RA diagnoses occurring between 1998 and 2013. RF was positive in 8.1% of cases with 10% of RF-positive subjects having HBsAg (p=0.004) and 9% anti-HCV. ACPA were detected in 4.8% of subjects with 5% of the ACPA-positive subjects having HBsAg and 5.9% anti-HCV. Older subjects had higher positivity rates for both RF and ACPA. HBsAg and anti-HCV were detected in 5.5% and 4.3% of sera, respectively. Over 15 years, 10 RA cases were recorded (9 women, median age at diagnosis 52 years) with RF previously positive in 2/10 and ACPA in 5/10 cases. RF and ACPA were associated with relative risks for developing RA of 5.7 (adjusted for HBsAg status; 95% CI 1.2-26.3) and 13.2 (95% CI 3.8-46.3), respectively. Our data in a large cohort from an unselected general population confirm a higher risk of RA development associated with ACPA compared to RF. HBV exposure correlates with RF but not with ACPA positivity.